(3aJM GdQMef HTQM RHO GHf QSdGfs - (3GdQedj, TgGH GdOjf, CMeO Hf CMeO Hf MeRI, J (B791 (3g`s ((3CHh HcQ Hf LGeY GdLHQJjs)
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdQedj GdMeO ddg GdPj HYK eMeO CeG HYO agPG TQM ddefXheI GdeSeGI HUahI GdRHO JCdja GHf QSdGf hSejJg aJM GdQMef HSe Gdg GdQMef GdQMje GdMeO ddg Pj GdLdGd hTGQY GdMQGe hGdMdGd GHJOGA HGdHSedI hGdMeO ddgs
(3BNQgG (B:s
(3hbhdg dg jdge HHfGjI ddaGYd Ch ddeaYhd aGdHMK Ydi GdChd efUhH hYdi GdKGfj eQahY haj HYV GdfSN jOd WQM JQcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1 / 94s
(3GdchGcH GdSGFQI (B2 / 144s
(3EjVGM Gdecfhf (B2 / 164s
(3TPQGJ GdPgH (B8 / 359s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs